2017
DOI: 10.1002/mame.201600363
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Surfaces through Immobilization of Self‐Assembled Polymer Architectures Using Thiol–Ene Chemistry

Abstract: An efficient strategy for engineering nanostructured surfaces by coupling soft polymeric nanoarchitectures to functionalized surfaces is presented. Self‐assembly of polymeric nanoarchitectures from amphiphilic triblock copolymers can yield both filled and hollow spherical nanoarchitectures, depending on the properties of the polymer chosen. These nanoarchitectures are immobilized on solid substrates via a biocompatible thiol–ene reaction, and conditions are optimized to maintain structural integrity of polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…Since our method is geared towards translational application, we have opted to immobilize our vesicles on glass, rather than much more expensive silicon wafers. As an attachment strategy, we used a thiol‐ene click chemistry procedure . Glass surfaces were solvent‐cleaned and activated in a plasma chamber, which generates reactive ‐OH groups on the surface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since our method is geared towards translational application, we have opted to immobilize our vesicles on glass, rather than much more expensive silicon wafers. As an attachment strategy, we used a thiol‐ene click chemistry procedure . Glass surfaces were solvent‐cleaned and activated in a plasma chamber, which generates reactive ‐OH groups on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…Next, the activated glass plates were functionalized using a 3‐(mercaptopropyl)trimethoxysilane linker. It was previously shown that the terminal thiol group of the selected linker reacts efficiently with the terminal methacrylate groups of the polymer . The reaction between the thiol groups on the glass substrate, and the methacrylate groups of polymer chains was performed in the presence of pH‐adjusted TCEP (tris(2‐carboxyethyl) phosphine hydrochloride) catalyst, thereby anchoring the nanocompartments to the glass surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface modification spans from chemical functionalization with small molecules that serve as initiators or reactive braces for self‐assembled monolayers (SAM). Common functionalization is based on highly reactive molecules that undergo high yielding chemistry, such as EDC/NHS, “Click,” thiol–ene, and Sn2 chemistry . Since the polymer chains are produced in advance, high control over the brush thickness is achieved by controlling the chain length.…”
Section: Planar Membrane Fabricationmentioning
confidence: 99%
“…The immobilization of nanostructures is performed either via non‐specific binding, or by covalent or supramolecular bonding . Among the three, the latter is preferred as it allows achieving higher control over the binding topology and distribution, as it has been reported by exploiting strain promoted click chemistry and thiol–ene reactions . The metal‐free highly reactive moieties (cyclooctine with azide) allowed the facile decoration of the PMOXA‐PDMS‐PMOXA assemblies on the surface.…”
Section: Planar Membrane Fabricationmentioning
confidence: 99%